Gas–liquid flow modeling in columns equipped with structured packing. Issue 10 (10th July 2014) - Soulaine, Cyprien; Horgue, Pierre; Franc, Jacques; Quintard, Michel
<x xml:space="preserve">Abstract</x> The modeling of gas–liquid flow in distillation columns equipped with structured packing has been dealt. The devices are seen as bistructured porous media, and a macroscale model is proposed taking into account this specific geometry. In this model, the two liquid films, one‐per‐sheet, are treated separately and are allowed to exchange matter at the vicinity of the contact points between corrugated sheets. The model emphasizes mechanisms that lead to the liquid radial dispersion effects: a main part comes from the geometry itself, another part is due to the capillary effects. A particular attention is paid to model these phenomena from a macroscale point of view. Finally, the simulation results are confronted to tomography imaging within a lab‐scale column and show a qualitative good agreement of the liquid distribution. © 2014 American Institute of Chemical Engineers AIChE J, 60: 3665–3674, 2014